Penerapan Etika Bisnis Islam Dalam Transaksi Jual Beli Pada Pedagang Pasar Tradisional (Studi Kasus di Pasar Makarti Jaya Kabupaten Banyuasin) - Eri Nur Azizah; Suryati Suryati; Candra Darmawan (Social Science and Contemporary Issues Journal, 2023)
Islamic business ethics is a set of values ​​about good and bad, right and wrong in running a business based on the principles of the Al-Qur'an and Hadith and those that have been exemplified by the prophet Muhammad SAW. This study aims to find out how the application of Islamic business ethics in buying and selling transactions at traditional market traders in Makarti Jaya sub-district, Banyuasin district. The method used in this research is descriptive qualitative method. The types of data used in this research are primary data and secondary data. In this study the data techniques used included observation and interviews. Based on the results of this study, it can be concluded that traders in the Makarti Jaya market have not fully implemented the principles of Islamic business ethics, especially in terms of the principles of justice and responsibility in providing quality goods, there are still traders who mix good quality and bad quality goods for sale, besides that lack of friendliness of traders to buyers, and there are still traders who force buyers to buy their wares. However, there are also traders who have applied the principles of Islamic business ethics, such as the principle of monotheism, in which traders continue to perform prayers in selling even though they cannot be on time, and compete fairly among fellow traders and provide payment grace periods to buyers.